Kehidupan Sosial Migran Madura di Desa Kintamani Tahun 1982-2018 - Yuliandri, Risa (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2021)
This study examines the Madurese community. The aim is to then find out the driving and pulling factors of Madurese migrating to Kintamani, knowing the sectors that Madurese are involved in, and the implications of Madurese migrants for the local community. The study uses historical methodology such as historical explanations. The result of this research is that the beginning of the migration of Madurese people, only a few Madurese immigrants who were in Kintamani, gradually as time went on the Madurese grew. Then Madurese can be accepted in Kintamani due to a factor when Madurese, who only a few come to Kintamani, participate in fighting for the village to give prizes in the form of land as usufructuary rights to Madurese and are only subject to funds according to the area obtained per family. Madurese people work in the field of business in general as traders and over time the Madurese community in Kintamani has grown and those who have succeeded already have permanent houses in Kintamani village.